1903. Cost Minimization Analysis of a Preferred ARV Prescribing Pathway for Treatment-Naïve HIV-Positive Patients. (26th November 2018) - Kerr, Colm; Allen, Niamh; Moynan, David; Moriarty, Miriam; Murphy, Sinead; Farrell, Gillian; Bergin, Colm
Abstract: Background: There were 266 new attendees to the HIV clinic of St. James' Hospital in 2016. HIV care is expensive. The modelled lifetime cost of treating one HIV-positive patient in the UK is estimated at £360, 800, with ARVs accounting for 68% of the cost. This audit aims to assess potential savings in ARV spend if a cost-based prescribing approach was adopted for suitable treatment-naïve patients of the clinic. Methods: A retrospective analysis of newly attending HIV-positive patients attending the HIV Clinic in 2016 was undertaken. Treatment-naïve patients were identified. 2016 ARV drug acquisition costs were obtained from the St. James' Hospital Finance department. The cost of first-line ARV regimens were calculated. Patients were evaluated for their suitability for the lowest-cost, first-line ARV regimen by analysing baseline viral loads, CD4 counts, resistance patterns, renal function, bone health and HLA B5701 status. The price difference between their prescribed regimens and the most cost-effective first-line regimen was calculated. Results: From January to December 2016, there were 266 new attendances. One hundered fifty-four of these patients (58%) were treatment naïve. The treatment regimens were ascertained for 145/154 (94%). A cost difference of approx. €390 per month existed between the most expensive and least expensive first-line ARV regimens. The monthly cost of ARV regimens prescribed came to €152, 949.09, equating to an annual spend of €1, 835, 389.08. The predicted monthly ARV cost of the cost-based prescribing approach has been calculated at €139, 186.27 with an annual cost of €1, 670, 235.24. This would lead to an annual saving of €165.153.84, equating to 9% of the 2016 ARV spend for this population. Conclusion: This audit outlines the potential cost-effectiveness of a cost-based prescribing approach for suitable treatment-naïve patients that also adheres to best clinical practice guidelines. It demonstrates that significant cost savings (9%) can be made by simple analysis of ARV costs. These data can be used to support future options in ARV procurement and tender-processing for the department and nationally. It can also serve as a template in the construction of a pathway for the safe and cost-effective switching of ARV regimens of patients already on established regimens when generic ARV medications become available in Ireland. Disclosures: All authors: No reported disclosures.